Menilai Efektivitas Aplikasi Sim Aset Pada Badan Pendapatan Pengelolaan Keuangan Aset Daerah Kabupaten X - Muhammad Rahadyan Widyadhana; Maulidyati Aisyah (Jurnal Mutiara Ilmu Akuntansi, 2023)
In an organization, SIM Asset is a very important part because it is a condition for decision making in the form of information or financial reports needed. As a way of knowing the value of the effectiveness of the information system that takes place at the Regional Asset Management Revenue Agency of X District. Researchers use the DeLone and McLean model with the aim of measuring the effect of system quality, information quality, and service quality on user satisfaction and use and find out the net result of use of the information system. By using Partial Least Square (PLS) there are 8 hypotheses tested. Of the 8 hypotheses that have been tested, six are accepted while two are rejected.